Pengaruh Harga dan Kualitas Pelayanan Jasa terhadap Kepuasan Keluarga Lansia di Panti Werdha Melania Pademangan ( Panti Non Mandiri ) Jakarta Utara - Skolastika Skolastika (Global Leadership Organizational Research in Management, 2024)
Melania Pademangan Nursing Home is a nursing home that cares for non-independent elderly. This research aims to analyze the influence of price and service quality on the satisfaction of non-independent elderly families at the Melania Pademangan nursing home, North Jakarta. The sample in this study was 36 respondents using saturated sampling techniques, the entire population in this study was used as the research sample. The data collection technique uses a questionnaire method with a Likert scale. Based on the results of this research, the price variable (X1) has a positive and significant influence on elderly family satisfaction (Y). The calculation results show that tcount > ttable (2.269 > 1.692) with a significance level of 0.030 < 0.05. The service quality variable (X2) has a positive and significant influence on elderly family satisfaction (Y). This is shown from the calculation results of tcount > ttable (6.127>1.692) with a significance level of 0.000 <0.05. Simultaneously, the price variable (X1) and the service quality variable (X2) have a positive and significant influence on elderly family satisfaction (Y). This was obtained from the calculation results of Fcount of 62,550 with a significance level of 0.000 < 0.05 and Fcount > Ftable (62.550 > 3.28). The results of the analysis of the coefficient of determination (R2) obtained an R Square of 0.791 or 79.1% influenced by the price variable (X1) and the service quality variable (X2) while the remaining 20.9% (100%-79.1%) was influenced by the variable other independent items not examined in this study.